2018
DOI: 10.1080/15583058.2018.1442528
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the seismic performance of historic timber buildings in Asia by applying super-elastic alloy to a Chinese complex bracket system

Abstract: Historic timber structures that are widely distributed in East Asia are suffering from the earthquakes. This research is aiming to develop a technique to enhance the seismic performance of historic timber buildings with Dou-Gon system. High strength steel bars and super-elastic alloy bars have been used instead of the conventional wood peg connection to connect the base Dou and the column. Pushover tests have been done under all loading conditions. The energy dissipation capacity and the ultimate strength of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…To enhance the damping ratio under heating, the SMA can be installed in a pre-strained form. In our previous studies [35,42], experiments showed that pre-strained SMAs can significantly increase the damping ratio. This solution ensures the SMA has sufficient damping.…”
Section: Discussion and Future Extensionsmentioning
confidence: 92%
See 1 more Smart Citation
“…To enhance the damping ratio under heating, the SMA can be installed in a pre-strained form. In our previous studies [35,42], experiments showed that pre-strained SMAs can significantly increase the damping ratio. This solution ensures the SMA has sufficient damping.…”
Section: Discussion and Future Extensionsmentioning
confidence: 92%
“…By contrast, under such a large deformation it is easy for traditional construction material such as steel to have a residual deformation. This could have a substantial effect on its stress-strain relationship and reduce its fatigue life [35]. Another advantage of SMA-based TMD is that it is mechanically simple.…”
Section: Figure 1 Idealisation Of the Application Of Tmd System To A Structurementioning
confidence: 99%
“…These timber buildings have diverse connection systems, such as dovetail connections (Chang & Hsu, 2005) and Dou-Gong system. The anti-seismic performance of historic timber buildings has been extensively studied over the past 20 years (Fang et al, 2001a;Fang et al, 2001b;Fujita, Hanazato & Sakamoto, 2004;Chang, 2005;Suzuki & Maeno, 2006;Chang, Hsu & Komatsu, 2006;Chang & Hsu, 2007;Yu et al, 2008;Chang et al, 2009;Xue et al, 2015;Yeo et al, 2018;Xie, Araki & Chang, 2018), and it has been recognised that Dou-Gong systems in historic timber buildings play an important role in resisting seismic action. Dou-Gong systems are located at the top of columns to support upper structures and transmit the weight of both the structures and the roof to the columns and the foundations.…”
Section: Introductionmentioning
confidence: 99%
“…A simple technique has been developed whereby metal bars are used to replace the conventional wooden peg connections to enhance the seismic performance of base Dou. It achieves this by maintaining base Dou's original re-centring capability and increasing both its energy dissipation capacity and its ultimate strength (Xie, Araki & Chang, 2018). Tests were conducted with conventional wooden peg connections and two metal connections (high strength steel and super-elastic alloy).…”
Section: Introductionmentioning
confidence: 99%